Gods, priests, and men : studies in the religion of pharaonic Egypt - Blackman, Aylward M. (Aylward Manley), 1883-1956 (Studies in Egyptology., 2011)
This volume brings together for the first time in a single volume the highly significant works on ancient Egyptian religion by Aylward Manley Blackman (1883-1956). Blackman's knowledge of Egyptian religion was unrivalled. He was best known for his series of studies on Egyptian religion which have long been regarded as essential reading in the subject, and which forms the content of the present collection. Unusually, Blackman did not publish his writings in book form, but preferred to place them in a wide range of publications that are extremely difficult to obtain. Blackman's studies on Egy.